Generalizability of developmental EEG: Demographic reporting, representation, and sample size - Santiago Morales; Lauren Oh; Kylie Cox; Ramiro Rodriguez-Sanchez; Gina Nadaya; George A. Buzzell; Sonya V. Troller-Renfree (Developmental Cognitive Neuroscience)
Electroencephalography (EEG) is one of the main neuroscientific measures used with infants and children to identify potential biomarkers of cognitive and social developmental processes. Given the implications of developmental EEG research within policy, clinical, and educational domains, it is important to ensure that reported results are generalizable and reproducible. In this review, to provide an initial assessment of previous and current practices regarding participant recruitment (sample size and representation) and demographic reporting, we carried out a systematic review of six notable journals for publishing pediatric EEG studies between 2011 and 2023. We identified 700 articles reporting on pediatric EEG. We found that most studies did not provide complete reporting of basic demographic information (e.g., race, ethnicity, socioeconomic status, geographical location). This trend persisted across years of publication, suggesting continued underreporting. However, the reporting of demographic information differed between journals, suggesting solutions for improving reporting practices. Our review also indicated that samples were of modest sample size (Median = 51) and consisted of mostly White participants (78 %) from North America and Western Europe (85 %). Our discussion emphasizes the need for larger, more diverse samples and greater transparency in developmental EEG studies, while providing recommendations to address barriers to representation and reproducibility.